Influence of Asthma Onset on Airway Dimensions on Ultra–high-resolution Computed Tomography in Chronic Obstructive Pulmonary Disease. Issue 4 (July 2021) - Tanabe, Naoya; Sato, Susumu; Oguma, Tsuyoshi; Shima, Hiroshi; Kubo, Takeshi; Kozawa, Satoshi; Koizumi, Koji; Sato, Atsuyasu; Togashi, Kaori; Matsumoto, Hisako; Hirai, Toyohiro
Abstract : Purpose: Asthma onset before the age of 40 years is associated with distinct clinical manifestations in chronic obstructive pulmonary disease (COPD) patients, but its morphologic features remain unestablished. This study aimed to explore airway morphology in COPD patients with asthma onset before 40 years of age using ultra–high-resolution computed tomography (U-HRCT), which allows a more accurate quantitation of the lumen and the wall in smaller airways than using conventional CT. Materials and Methods: Clinical data of 500 consecutive patients undergoing full inspiratory U-HRCT (1024×1024 matrix and 0.25 mm slice thickness) were retrospectively analyzed. COPD patients without asthma, COPD patients with asthma onset at age below or 40 years and above, and non-COPD smoker controls (N=137, 29, 34, and 22, respectively) were enrolled. The length, lumen area (LA), wall thickness and area (WA), and wall area percent (WA%) of the segmental (third-generation) to sub-subsegmental (fifth-generation) bronchus and the low attenuation volume percent (LAV%) were measured. Results: LA and WA were smaller in the fourth and fifth generation in COPD patients than in non-COPD controls, regardless of the age of asthma onset. LA was smaller and WA% was larger in the fourth-generation and fifth-generation airways in COPD with asthma onset before 40 years than COPD without asthma, whereas WA did not differ between them. In multivariate analyses, asthma onset before 40 years was associated with smaller LA in COPD patients independent of demographics, use of inhaled corticosteroids and long-acting bronchodilators, airflow limitation, and LAV%. Conclusions: Asthma onset before 40 years of age could be associated with greater lumen narrowing of the airways in COPD. Abstract : Supplemental Digital Content is available in the text.